Hubungan Status Gizi dengan Perkembangan Anak Umur 24-60 Bulan di Kelurahan Bener Kota Yogyakarta - Reni Merta Kusuma (Jurnal Kesehatan Vokasional, 2019)
Background: Toddler growth and development monitoring is required. The growth is increasing the size of the cells, cell count, and intracellular tissue. Physical changes associated with growth and body structure. The progression is the increase of the function of the structure and function of the body. Growth and development of coupled, so it is important to monitor. The importance of monitoring the growing swell toddlers, researchers want to find out the correlation of these two variables.Objective: To find out the relationship between nutritional status and development of infants in Bener Village, Yogyakarta CityMethods: The draft cross-sectional study with data capture at any given moment. The population of a number of 84 children aged 24-60 months. The sampling techniques used total sampling so that the sample amounted to 84. The data obtained will be analyzed by testing the continent Koefisiensi test with Pearson Correlation Lamda.Results: The research results showed that the nutritional status of children aged 24-60 months in Kelurahan Bener 81% 3.6% normal and stated stated skinny as hell. Development of a toddler aged 24-60 months in Kelurahan Bener 89.3% 2.4% expressed and revealed irregularities. Bivariat analysis results declared between nutritional status with the development of a toddler aged 24-60 months value p of 0.493. Position korelasinya is very weak with the value of the correlation of Pearson of 0.076.Conclusion: Conclusion there is no relationship of nutritional status with the development of a toddler aged 24-60 months and correlation of both positions is very weak.